Anterior Interosseous Nerve Palsy After Shoulder Arthroscopy Treated With Surgical Decompression: A Case Series and Systematic Review of the Literature. (March 2021) - Nammour, Michael; Desai, Bhumit; Warren, Michael; Sisco-Wise, Leslie
Background: Anterior interosseous nerve (AIN) palsy is a very uncommon cause of upper extremity pain and weakness that comprises less than 1% of all upper extremity nerve palsies. Rarely reported but also mentioned in the literature is AIN palsy after shoulder arthroscopy.Methods: A systematic review of the literature to date using PubMed was conducted to identify patients who suffered AIN palsy after shoulder arthroscopy procedures. Articles included met the following criteria: (1) published in English; (2) primary presentation of the data; (3) patients had undergone shoulder arthroscopy before developing symptoms of AIN palsy; and (4) diagnosis was confirmed with clinical symptoms of AIN palsy. Measured outcomes included patient demographics, specific shoulder procedure, anesthesia procedure, intra-operative patient positioning, intra-operative compressive dressing, intra-operative traction, surgical versus conservative treatment, abnormal findings during decompression procedure, proposed mechanism of injury, and follow-up.Results: The search yielded 6 articles, of which 4 (13 cases) met inclusion criteria. An additional 2 cases were included in this report totaling 15 cases. The average patient age was 49 years (range: 31-64) with 73% males. At average follow-up of 24 months, 67% of patients experienced complete resolution of symptoms—more than half of which underwent surgical decompression. Patients who failed to progress experienced weakness of the flexor digitorum profundus and flexor pollicis longus muscles.Conclusions: Proposed injury mechanisms for AIN palsy after shoulder arthroscopy range from mechanical trauma, compressive hematoma, and direct anesthetic neurotoxicity. Management should be directed by clinical symptoms, imaging, and patient factors with majority of patients expected to have excellent clinical outcomes.